Preparation method of laser bar heat sink sheet with high thermal conductivity and low thermal expansion

By combining copper or copper alloy on the sheet-shaped artificial diamond surface of the laser bar heat sink, and combining magnetron sputtering method and vacuum hot pressing sintering technology, the low thermal conductivity and thermal expansion coefficient mismatch in the prior art are solved. Problem: A laser bar heat sink with high thermal conductivity and low thermal expansion has good processability and suitable large-scale production characteristics.

CN119426815AActive Publication Date: 2025-02-14YANGTZE OPTICAL FIBRE & CABLE CO LTD

Patent Information

Application Number
CN202411579488.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The overall thermal conductivity of existing laser bar heat sinks is low, the thermal expansion coefficient does not exactly match the chip, and the processability is poor, which affects the performance and processability of the product.

Method used

Using sheet-shaped artificial diamond as the core, the surface is composited with copper or copper alloy, and metal chromium or titanium is coated by magnetron sputtering to form an active brazed metal layer, and vacuum hot pressing and sintering is carried out in combination with graphite mold to form high thermal conductivity and low thermal expansion laser bar heat sink.

Benefits of technology

It significantly improves the overall thermal conductivity of the laser bar heat sink, while maintaining a suitable thermal expansion coefficient, improving the processability of the product, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119426815A_ABST
    Figure CN119426815A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a laser bar heat sink sheet with high thermal conductivity and low thermal expansion. The preparation method comprises the following steps: cutting a sheet-shaped artificial diamond into a laser bar heat sink sheet core material in a laser cutting manner; plating metal chromium or titanium on the surface of the core material by adopting a magnetron sputtering method, and coating a layer of active brazing metal on the surface of the core material to form a core material inner mold; a graphite die provided with a plurality of through hole arrays is adopted, and each through hole is provided with an upper graphite pressure head and a lower graphite pressure head; combining and coating the core material inner mold with a matched metal shell and a matched cover plate, then placing the core material inner mold in the through hole, and assembling an upper graphite pressure head and a lower graphite pressure head to form a template assembly; carrying out vacuum hot pressing sintering on the template assembly to obtain a laser bar heat sink blank, and grinding and polishing to obtain a laser bar heat sink finished product; according to the obtained product, the flaky artificial diamond serves as a core, copper or copper alloy is compounded on the surface, the overall heat conductivity of the product is further improved, meanwhile, the proper thermal expansion coefficient is guaranteed, the machinability is good, and the method is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite materials, and in particular relates to a method for preparing a high thermal conductivity and low thermal expansion laser bar heat sink. Background Art

[0002] With the rapid development of semiconductor laser technology and the continuous expansion of its application fields, high-power semiconductor lasers are widely used in laser processing, laser medical treatment, laser communication, national defense and military industries, etc. When a high-power semiconductor laser is working, a large amount of heat will be generated in the active area. If it is not dissipated in time, it will seriously affect the output power, electro-optical conversion efficiency and service life of the laser. The more mature heat sink materials on the market today, such as aluminum nitride, tungsten copper alloy, molybdenum copper alloy, etc., although their thermal expansion coefficients are close to those of chips, their thermal conductivity is low and their heat dissipation capacity is limited. Diamond is the substance with the highest thermal conductivity in nature, with a maximum of 2200W / (mK), and its lowest thermal expansion coefficient is only 0.8×10 -6 / ℃. Therefore, with artificial diamond as the core and suitable metal materials composited on the surface, a heat sink with high thermal conductivity and low thermal expansion coefficient can be prepared to meet the thermal management requirements of high-power semiconductor lasers.

[0003] Patent CN117340256A discloses a method for preparing a laser bar heat sink, which uses a molybdenum alloy or a tungsten alloy as a template, fills the core with coated diamond particles wrapped by copper powder and copper alloy powder, and forms a surface molybdenum alloy or tungsten alloy after hot pressing and sintering, and the core is a diamond / copper composite material structure. The thermal conductivity of the diamond / copper composite material is generally 500-800W / (mK), and the thermal expansion coefficient is (6-8)×10 -6 / ℃, coating the surface with molybdenum alloy or tungsten alloy will significantly reduce the overall thermal conductivity of the product. At the same time, the thermal expansion coefficient of the selected molybdenum alloy or tungsten alloy should also be within 8×10 -6 / ℃ or below to ensure the overall thermal expansion coefficient matches the chip. In addition, using molybdenum alloy or tungsten alloy as a template is prone to deformation under high temperature and high pressure, resulting in changes in geometric dimensions, making processing and positioning difficult, and making the thickness of the six-sided metal layer of the finished product uneven.

[0004] How to further improve the overall thermal conductivity of the product and ensure a suitable thermal expansion coefficient while having good processability has become a technical problem that needs to be solved urgently. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a high thermal conductivity and low thermal expansion laser bar heat sink. The obtained product has a sheet-like artificial diamond as the core and is composited with copper or copper alloy on the surface, which further improves the overall thermal conductivity of the product while ensuring a suitable thermal expansion coefficient. It has good processability and is suitable for large-scale production.

[0006] In order to achieve the above purpose, the technical solutions adopted are as follows:

[0007] A method for preparing a high thermal conductivity and low thermal expansion laser bar heat sink comprises the following steps:

[0008] (1) Cutting the sheet-like artificial diamond into laser bar heat sink core material by laser cutting;

[0009] (2) using magnetron sputtering to plate metal chromium or titanium on the surface of the core material, and coating the surface of the core material with a layer of active brazing metal to form a core material inner mold;

[0010] (3) using a graphite mold with a plurality of through-hole arrays, and each through-hole is equipped with an upper and lower graphite pressure head; the core material inner mold is combined with a matching metal shell and a cover plate and then placed in the through-hole, and the upper and lower graphite pressure heads are assembled to form a template assembly;

[0011] (4) The template assembly is vacuum hot-pressed and sintered to obtain a laser bar heat sink blank, and the laser bar heat sink finished product is obtained through grinding and polishing.

[0012] According to the above scheme, the thermal conductivity of the flake-shaped artificial diamond in step (1) is 800-2200 W / (mK), and the thermal expansion coefficient is 0.8-4×10 -6 / ℃, thickness 0.3~3.0mm. Specifically, high thermal conductivity, low thermal expansion artificial diamond sheet and its composite sheet can be used.

[0013] According to the above scheme, step (1) further includes mechanical grinding and polishing of the core material to remove graphite generated on the surface of the flaky artificial diamond core material due to laser cutting, thereby avoiding the adverse effect of free carbon on the interface bonding.

[0014] According to the above scheme, in step (2), the thickness of the metal chromium or titanium coating by magnetron sputtering is 50-500nm. The core material surface coating can improve the wettability between metal and diamond, enhance the interface bonding strength, and reduce the thermal damage of the core material at high temperature.

[0015] According to the above scheme, the active brazing metal in step (2) is a chromium-containing or titanium-containing brazing sheet, specifically any one of Cu-Sn-Cr, Ag-Cu-Cr, Cu-Sn-Ti, and Ag-Cu-Ti, and the brazing sheet has a thickness of 0.01 to 0.5 mm.

[0016] According to the above scheme, the coating method used in step (2) includes: stamping the active brazing sheet into a cup shape or sheet shape matching the core material, and pressing and coating the active brazing sheet on the surface of the core material.

[0017] According to the above scheme, the metal shell and cover plate described in step (3) are made of one of pure copper, molybdenum-copper alloy and tungsten-copper alloy; wherein the molybdenum content of the molybdenum-copper alloy is 30-80wt%, and the rest is copper; the tungsten content of the tungsten-copper alloy is 30-80wt%, and the rest is copper.

[0018] According to the above scheme, the thickness of the bottom and cover of the metal shell in step (3) is 0.1-1.0 mm, and the wall thickness of the four sides of the shell is 1.0-5.0 mm.

[0019] According to the above scheme, the vacuum hot pressing sintering in step (4) includes: evacuating to 10 -1 ~10 -2 Pa, heat up to 750-850℃ at 5-10℃ / min, keep warm for 30-60min, and pressurize to 1-10MPa while keeping warm; continue to heat up to 850-1000℃ at 1-5℃ / min, and keep warm for 10-30min.

[0020] According to the above scheme, the outer metal thickness of the finished laser bar heat sink obtained in step (4) is 0.05-0.5 mm.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] By using artificial diamond sheets or their composite sheets with higher thermal conductivity and lower thermal expansion coefficient as the core, the composition and thickness of the surface composite metal material have greater flexibility, and a laser bar heat sink with higher overall thermal conductivity and lower thermal expansion coefficient can be obtained.

[0023] The active brazing metal composite core material and surface metal can form a good bond with the core material and the surface metal, and can also reduce the temperature and time of vacuum hot pressing, reducing the thermal damage of diamond. In addition, the six sides of the core material are completely covered with active brazing metal and placed in the six-sided cavity formed by the copper or copper alloy shell and cover plate, which is not easy to produce bonding defects such as pores.

[0024] The laser bar heat sink blank of the present invention is assembled one by one from core material, active brazing metal, copper or copper alloy shell and cover plate, and graphite with good high temperature strength is used as the mold. The blank has good size consistency after vacuum hot pressing, and the finished product can be obtained through symmetrical grinding and polishing. The thickness of the six-sided metal layer of the finished product is uniform, the preparation process is simple, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 : A schematic structural diagram of the core material inner mold of the present invention.

[0026] Figure 2 : Schematic diagram of the assembly structure of a single through hole of the template assembly of the present invention.

[0027] Figure 3 : Schematic diagram of the template assembly of the present invention. DETAILED DESCRIPTION

[0028] The following examples further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.

[0029] Example 1

[0030] 1) The thickness of the artificial diamond multi-crystalline wafer is 0.8 mm, the thermal conductivity is 1053 W / (mK), and the thermal expansion coefficient is 1.2×10 -6 / ℃; cut into core materials with a size of 9.6×4.6×0.8mm by laser; put the core materials into a grinding and polishing machine for 10 minutes, and then clean the core materials with deionized water and alcohol in turn.

[0031] 2) The core material surface is coated with 100 nm thick metal chromium by magnetron sputtering.

[0032] 3) Select a Cu-Sn-Cr active brazing sheet with a thickness of 0.05 mm and punch it into a cup-shaped part and a sheet-shaped part matching the core material in step 1); Figure 1 As shown, the core material 33 and the sheet-like part 31 are sequentially placed in the cup-shaped part 32, and the cup mouth is pressed inward to form a core material inner mold.

[0033] 4) Use pure copper to process into a shell and cover plate that matches the core inner mold. The thickness of the shell bottom and cover plate is 0.5mm, and the wall thickness of the four sides of the shell is 2mm; use graphite to process into a graphite mold with several through-hole arrays, such as Figure 3 As shown, the size of each through hole matches the shell and is equipped with graphite upper and lower pressure heads; Figure 2 As shown, the lower graphite pressing head 5, the copper shell 4, the core material inner mold 3, the copper cover plate 2, and the upper graphite pressing head 1 are assembled and placed into each through hole of the graphite mold 6 to form a template assembly.

[0034] 5) Place the template assembly into a vacuum hot pressing furnace for hot pressing sintering. The process conditions are: vacuum pumped to 5×10 - 1 Start heating below Pa; increase the temperature to 800℃ at 10℃ / min, keep it at that temperature for 30min, and increase the pressure to 3MPa while keeping it at that temperature; continue to increase the temperature to 950℃ at 5℃ / min, and keep it at that temperature for 10min.

[0035] 6) The graphite mold and the upper and lower graphite pressing heads are removed to obtain a blank, and the blank is ground and polished to obtain a finished laser bar heat sink sheet with a size of 10×5×1.2 mm, and the thickness of the six-sided copper layer is 0.2 mm.

[0036] The comprehensive thermal conductivity of the laser bar heat sink is 673W / (mK), and the average thermal expansion coefficient at 25-100℃ is 7.5×10 -6 / ℃.

[0037] Example 2

[0038] 1) The thickness of the artificial diamond multi-crystalline wafer is 0.8 mm, the thermal conductivity is 1053 W / (mK), and the thermal expansion coefficient is 1.2×10 -6 / ℃; cut into core materials with a size of 9.6×4.6×0.8mm by laser; put the core materials into a grinding and polishing machine for 10 minutes, and then clean the core materials with deionized water and alcohol in turn.

[0039] 2) The core material surface is coated with 50 nm thick titanium by magnetron sputtering.

[0040] 3) Select a Cu-Sn-Ti active brazing sheet with a thickness of 0.05 mm, and punch it into a cup-shaped part and a sheet-shaped part that match the core material in step 1); put the core material and the sheet-shaped part into the cup-shaped part in sequence, and press the cup mouth inward to form a core material inner mold.

[0041] 4) A molybdenum-copper alloy with a molybdenum content of 40wt% is selected to be processed into a shell and a cover plate that match the core inner mold, the thickness of the shell bottom and the cover plate is 0.5mm, and the wall thickness of the four sides of the shell is 2mm; graphite is used to be processed into a graphite mold with a plurality of through-hole arrays, the size of each through-hole matches the shell, and is equipped with upper and lower graphite pressure heads; the lower graphite pressure head, the molybdenum-copper alloy shell, the core inner mold, the molybdenum-copper alloy cover plate, and the upper graphite pressure head are assembled and placed in each through-hole of the graphite mold to form a template assembly.

[0042] 5) Place the template assembly into a vacuum hot pressing furnace for hot pressing sintering. The process conditions are: vacuum pumped to 5×10 - 1 Start heating below Pa; increase the temperature to 800℃ at 10℃ / min, keep it warm for 30min, and increase the pressure to 5MPa while keeping it warm; continue to increase the temperature to 900℃ at 5℃ / min, and keep it warm for 10min.

[0043] 6) The graphite mold and the upper and lower graphite pressing heads are removed to obtain a blank, and the blank is ground and polished to obtain a finished laser bar heat sink with a size of 10×5×1.2 mm, and the thickness of the six-sided molybdenum-copper alloy layer is 0.2 mm.

[0044] The comprehensive thermal conductivity of the laser bar heat sink is 604W / (mK), and the average thermal expansion coefficient at 25-100℃ is 6.3×10 -6 / ℃.

[0045] Example 3

[0046] 1) The thickness of the artificial diamond multi-crystalline wafer is 1.6 mm, the thermal conductivity is 931 W / (mK), and the thermal expansion coefficient is 1.4×10 -6 / ℃; cut into core materials with a size of 9.6×4.6×1.6mm by laser; put the core materials into a grinding and polishing machine for 10 minutes, and then clean the core materials with deionized water and alcohol in turn.

[0047] 2) The core material surface is coated with 50 nm thick titanium by magnetron sputtering.

[0048] 3) Select a Cu-Sn-Ti active brazing sheet with a thickness of 0.05 mm, and punch it into a cup-shaped part and a sheet-shaped part that match the core material in step 1); put the core material and the sheet-shaped part into the cup-shaped part in sequence, and press the cup mouth inward to form a core material inner mold.

[0049] 4) A tungsten-copper alloy with a tungsten content of 50wt% is selected to be processed into a shell and a cover plate that match the core inner mold, the thickness of the shell bottom and the cover plate is 0.5mm, and the wall thickness of the four sides of the shell is 2mm; graphite is used to be processed into a graphite mold with a plurality of through-hole arrays, the size of each through-hole matches the shell, and is equipped with upper and lower graphite pressure heads; the lower graphite pressure head, tungsten-copper alloy shell, core inner mold, tungsten-copper alloy cover plate, and upper graphite pressure head are combined and placed in each through-hole of the graphite mold to form a template assembly.

[0050] 5) Place the template assembly into a vacuum hot pressing furnace for hot pressing sintering. The process conditions are: vacuum pumped to 5×10 - 1 Start heating below Pa; increase the temperature to 800℃ at 10℃ / min, keep it warm for 30min, and increase the pressure to 5MPa while keeping it warm; continue to increase the temperature to 900℃ at 5℃ / min, and keep it warm for 10min.

[0051] 6) The graphite mold and the upper and lower graphite pressing heads are removed to obtain a blank, and the blank is ground and polished to obtain a finished laser bar heat sink with a size of 10×5×2.0 mm, and the thickness of the six-sided tungsten-copper alloy layer is 0.2 mm.

[0052] The comprehensive thermal conductivity of the laser bar heat sink is 559W / (mK), and the average thermal expansion coefficient at 25-100℃ is 5.8×10 -6 / ℃.

Claims

1. A method for preparing a high thermal conductivity and low thermal expansion laser bar heat sink, characterized in that Includes steps: (1) Cutting the sheet-like artificial diamond into laser bar heat sink core material by laser cutting; (2) using magnetron sputtering to plate metal chromium or titanium on the surface of the core material, and coating the surface of the core material with a layer of active brazing metal to form a core material inner mold; (3) using a graphite mold with a plurality of through-hole arrays, and each through-hole is equipped with an upper and lower graphite pressure head; the core material inner mold is combined with a matching metal shell and a cover plate and then placed in the through-hole, and the upper and lower graphite pressure heads are assembled to form a template assembly; (4) The template assembly is vacuum hot-pressed and sintered to obtain a laser bar heat sink blank, and the laser bar heat sink finished product is obtained through grinding and polishing.

2. The method for preparing the high thermal conductivity and low thermal expansion laser bar heat sink as claimed in claim 1, characterized in that The thermal conductivity of the flake-shaped artificial diamond in step (1) is 800 to 2200 W / (mK), and the thermal expansion coefficient is 0.8 to 4×10 -6 / ℃, thickness 0.3~3.0mm.

3. The method for preparing the high thermal conductivity and low thermal expansion laser bar heat sink as claimed in claim 1, characterized in that Step (1) also includes mechanical grinding and polishing of the core material.

4. The method for preparing the high thermal conductivity and low thermal expansion laser bar heat sink as claimed in claim 1, characterized in that Step (2) The metal chromium or titanium is plated by magnetron sputtering to a coating thickness of 50 to 500 nm.

5. The method for preparing the high thermal conductivity and low thermal expansion laser bar heat sink as claimed in claim 1, characterized in that The active brazing metal in step (2) is a brazing sheet containing chromium or titanium, specifically any one of Cu-Sn-Cr, Ag-Cu-Cr, Cu-Sn-Ti, and Ag-Cu-Ti, and the brazing sheet has a thickness of 0.01 to 0.5 mm.

6. The method for preparing the high thermal conductivity and low thermal expansion laser bar heat sink as claimed in claim 1, characterized in that The coating method used in step (2) includes: stamping the active brazing sheet into a cup shape or sheet shape matching the core material, and pressing and coating the active brazing sheet on the surface of the core material.

7. The method for preparing the high thermal conductivity and low thermal expansion laser bar heat sink as claimed in claim 1, characterized in that The metal shell and cover plate described in step (3) are made of one of pure copper, molybdenum-copper alloy and tungsten-copper alloy; wherein the molybdenum content of the molybdenum-copper alloy is 30-80wt%, and the rest is copper; the tungsten content of the tungsten-copper alloy is 30-80wt%, and the rest is copper.

8. The method for preparing the high thermal conductivity and low thermal expansion laser bar heat sink as claimed in claim 1, characterized in that The thickness of the bottom and cover of the metal shell in step (3) is 0.1-1.0 mm, and the wall thickness of the four sides of the shell is 1.0-5.0 mm.

9. The method for preparing the high thermal conductivity and low thermal expansion laser bar heat sink as claimed in claim 1, characterized in that The vacuum hot pressing sintering in step (4) includes: evacuating to 10 -1 ~10 -2 Pa, heat up to 750-850℃ at 5-10℃ / min, keep warm for 30-60min, and pressurize to 1-10MPa while keeping warm; continue to heat up to 850-1000℃ at 1-5℃ / min, and keep warm for 10-30min.

10. The method for preparing the high thermal conductivity and low thermal expansion laser bar heat sink as claimed in claim 1, characterized in that The outer metal thickness of the finished laser bar heat sink obtained in step (4) is 0.05 to 0.5 mm.

Citation Information

Patent Citations

  • Preparation method of laser bar heat sink sheet

    CN117340256A

  • Method for preparing high-heat-conductivity diamond copper-base composite material through super-high-pressure sintering

    CN102586641A

  • Diffusion bonding method of diamond micro-channel

    CN111843165A

  • Chip anti-reverse packaging structure and method

    CN113675153A

  • Strain relieving transition member for contacting semiconductor devices

    US3387191A

Cited By

  • Brazing method for titanium alloy

    CN119973268A